Managerial Proactiveness, Frugal Innovation and Firm Performance - Mir Dost; Waheed Ali Umrani
Firms use frugal innovations$1 (Baffordable, functional and long-lasting solutions$1 (Bto address issues in developing markets. These innovations aid businesses in providing valuable customer services, opening new markets and achieving sustainable goals that add value and stimulate the economy. However, our understanding of the link between frugal innovation and business performance is limited. To address this issue, the authors used a resource-based view and stakeholder theories to investigate the link between frugal innovation and firm financial and environmental performance and the moderating role of managerial proactiveness. The study analysed data from 580 CEOs in emerging markets, and the findings revealed that frugal innovation significantly enhances a firm$1 (Bs financial and environmental performance. Managerial proactiveness also moderates the impact of frugal innovation on financial and environmental performance. The article concludes by discussing the theoretical and managerial implications, highlighting the importance of frugal innovation and the role of managerial proactiveness in driving firm performances